Galvanic corrosion of duplex corrosion-resistant steel rebars under carbonated concrete conditions. Issue 30 (4th May 2018) - Jiang, Jinyang; Chu, Hong-yan; Liu, Yao; Wang, Danqian; Guo, Dong; Sun, Wei
Abstract : Galvanic corrosion between two different kinds of steel rebars is usually the case in practical engineering. Abstract : Galvanic corrosion between two different kinds of steel rebars is usually the case in practical engineering. Open circuit potential (OCP), linear polarization resistance (LPR), Tafel polarization, scanning vibrating electrode technique (SVET), scanning electron microscopy (SEM) and reflection digital holographic microscopy (DHM) were used to study the galvanic corrosion of a novel corrosion-resistant steel bar (CR) and low-carbon steel bar (LC) in simulated concrete pore solutions with different pH values and a chloride ion concentration of 5 mol L −1 . The pH of the simulated concrete pore solution had a significant impact on the corrosion behaviour of CR and LC when they were in contact and were attacked by chloride ions. As the pH increased, the potential between CR and LC decreased and the driving force for the galvanic corrosion decreased. When the pH was 9.0, galvanic corrosion occurred on CR and LC at a high rate. CR developed local pitting corrosion, while LC mainly developed uniform corrosion, each with an apparent accumulation of corrosion products on the sample's surfaces. When the pH was 11.3, galvanic corrosion occurred when CR and LC were in contact. CR showed a relatively smooth surface, with only a small amount of pitting corrosion. In contrast, LC developed both pitting corrosion and uniform corrosion, and both apparent pitting corrosion and an accumulation of corrosion products on the sample surface were observed. When the pH was 13.6, there was no galvanic corrosion when CR and LC were in contact; the corrosion of CR and LC was mainly pitting corrosion. Therefore, for regions with chloride ion corrosion and severe carbonization, the galvanic corrosion between CR and LC cannot be ignored.